(untitled) (Eurasian Journal of Ecology, 2023)
Recently, special attention should be paid to the effective use of agricultural land to prevent food shortages, which may arise both in the world and in our republic. For this reason, it is very important to study the processes of magmatism in the Nakhchivan MR, where lands unsuitable for the development of agrocenoses occupy a large area. Various categories of risks and hazards caused by the influence of magmatism processes were calculated by performing certain calculations through the GIS program. Effusive and intrusive magmatic processes have created conditions for the creation of various landforms on the earth’s surface. At the same time, the scale of these underground processes in the area of our research determined the diversity of minerals and the abundance of mineral waters. This has led to the acquisition of important land for the development of agrocenoses in various sectors of our research area, which has led to an increase in risks and dangers. He calculated the risks and hazards caused by magmatism in the area in different categories. The study of magmatism processes is very important when placing any infrastructure object. This is of practical importance for accommodating the various agricultural fields that currently exist and will be established in the future in the area where we are conducting research. Key words: magmatic processes, agrocenoses, relief, intrusion, effusive, morphostructure